Scientific production on smart cities in Brazil: Bibliometric mapping of BDTD dissertations (2013 to 2023) - Carneiro, Adrielly Oliveira; Giacaglia, Marcelo Eduardo (National Journal of City Management, 2025)
Objective – This study aims to outline the constitution of the scientific field on "smart cities" in Brazil, Methodology – Bibliometric analysis of 40 dissertations defended between 2013 and 2023. A comprehensive bibliometric mapping was carried out, focusing on variables such as: a) temporal evolution; b) geographical and institutional distribution; c) most covered topics. Originality/Relevance – The study provides a broad and unprecedented perspective on the academic development of the smart cities theme in Brazil.Results – The findings indicate a significant growth in academic production on smart cities during the analysed period, along with thematic concentration in postgraduate programmes in Administration, Electrical Engineering, and Computer Engineering.Theoretical/Methodological Contributions – The bibliometric analysis applied to the Brazilian context offers an effective tool to map research trends and identify scientific gaps.Social and Environmental Contributions – The study highlights the need for deeper exploration of topics such as public safety, privacy, active social participation, sustainability, and economic impacts, which are crucial for developing more inclusive and resilient smart cities.
Keywords: Smart cities; Scientific Communications; Brazil